+0  
 
-1
132
1
avatar+851 

Suppose that $f$ is a function and $f^{-1}$ is the inverse of $f$. If $f(3)=4$, $f(5)=1$, and $f(2)=5$, evaluate $f^{-1}\left(f^{-1}(5)+f^{-1}(4)\right)$.

Lightning  Jul 15, 2018
 #1
avatar+20744 
+1

Suppose that $f$ is a function and $f^{-1}$ is the inverse of $f$. If $f(3)=4$, $f(5)=1$, and $f(2)=5$,
evaluate $f^{-1}\left(f^{-1}(5)+f^{-1}(4)\right)$.

 

\(\begin{array}{|r|r|r|r|} \hline x & f(x) \\ \hline 2 & 5 & f(2) = 5 & f^{-1}(5) = 2 \\ 3 & 4 & f(3) = 4 & f^{-1}(4) = 3 \\ 5 & 1 & f(5) = 1 & \\ \hline f^{-1}(x) & x \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline && f^{-1}\Big(f^{-1}(5)+f^{-1}(4)\Big) \\ &=& f^{-1}\left(2+3\right) \\ &=& f^{-1}(5) \\ &=& 2 \\ \hline \end{array}\)

 

 

laugh

heureka  Jul 16, 2018

5 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.